Glutamina e Nucleotídeos na Dieta de Frangos de Corte Criados no Sistema Alternativo - Zavarize, K. C. [UNESP]; Sartori, José Roberto [UNESP]; Pelícia, V. C. [UNESP]; Pezzato, Antonio Celso [UNESP]; Araujo, P. C. [UNESP]; Stradiotti, A. C. [UNESP]; Madeira, L. A. [UNESP] (My University, 2011)
The experiment was conducted to evaluate the effect of supplementing glutamine and nucleotides on growth performance and development intestinal morphology in broiler chicks. In the trial, 600 male broiler chicks distributed in randomized blocks in a 3x2 factorial arrangement (consisting of a uniform basal diet supplemented with: 0.0, 0.5 or 1.0% glutamine, and 0.0 or 0.04% nucleotides), for a total of 6 treatments with 25 birds each. Means of performance (weight, weight gain, feed intake, feed conversion and mortality) were obtained 7, 21 and 42 days of age. At the end of the experiment 4 broilers per treatment were used to determine organs weight and development intestinal morphology. Glutamine supplementation (1%) improved the body weight, feed intake and feed conversion in the first week. Glutamine and nucleotides supplementation did not affect performance in broiler chicks in the period one to 21 and one to 42 days of age. In conclusion, it was demonstrated that feeding 1.0% glutamine improved growth performance of broiler birds at 21 days of age.
Glutamine and nucleotide supplementation in broiler diets in alternative breeding system
Keywords: Intestinal morphology; Performance; Aves